EDITORIAL: Media and free expression - David Robie (Asia Pacific Network, 1999)
When rumours abounded in December 1998 about the impending sale of Papua New Guinea's Post-Courier, arguably the best daily newspaper in the South Pacific, to a consortium headed by a crony Prime Minister Bill Skate  the Port Moresby media world was in a spin. It turned out to be a false alarm. However, when controlling shares in the long-struggling Fiji Daily Post were abruptly sold in Feburary 1999 to the Fiji Government, it was a different story. Protests from other media organisations were also strong—but too late.